2023
DOI: 10.3390/polym15040861
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Fiber Orientation on Mechanical and Elastic Characteristics at Axial Stresses of GFRP Used in Wind Turbine Blades

Abstract: Due to its physical and mechanical properties, glass-fiber-reinforced polymer (GFRP) is utilized in wind turbine blades. The loads given to the blades of wind turbines, particularly those operating offshore, are relatively significant. In addition to the typical static stresses, there are also large dynamic stresses, which are mostly induced by wind-direction changes. When the maximum stresses resulting from fatigue loading change direction, the reinforcing directions of the material used to manufacture the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The experimental protocol involved presenting each specimen to a strain rate of 0.5 mm/min until failure. The mechanical properties under consideration, including Yield Tensile Strength and Ultimate Tensile Strength, were evaluated via tensile testing conducted in accordance with ASTM B557-15 [38,39].…”
Section: Tensile Testmentioning
confidence: 99%
“…The experimental protocol involved presenting each specimen to a strain rate of 0.5 mm/min until failure. The mechanical properties under consideration, including Yield Tensile Strength and Ultimate Tensile Strength, were evaluated via tensile testing conducted in accordance with ASTM B557-15 [38,39].…”
Section: Tensile Testmentioning
confidence: 99%
“…The frequent movement of yaw results in long-term and unbalanced force loads on wind turbine blades, leading to fatigue accumulation [6], which may potentially cause structural damage to the blades, resulting in cracks and damages that may shorten its expected service life. Research on large wind turbines has shown that the accurate failure location of blades is generally at the stress concentration location [7]. Therefore, the study of blade stress under yaw conditions has a direct and important impact on the reliability and lifespan of wind turbine blades.…”
Section: Introductionmentioning
confidence: 99%